Comparative study on combustion and emission of SI engine blended with HHO by different injection modes of gasoline. (19th September 2022) - Zhao, Zhe; Huang, Yan; Yu, Xiumin; Li, Ming; Zhang, Zhihong; Guo, Zezhou; Wang, Tianqi; Li, Decheng
Abstract: As a hydrogen fuel for real-time production without storage, HHO has great research prospect and significance. In this paper, we conducted experiments on a spark ignition (SI) engine which has two independent fuel supply systems to compare two combination modes of gasoline port injection plus HHO (GPI + HHO) and gasoline direct injection plus HHO (GDI + HHO) at different HHO flow rate, λ, engine speed and load. The results show that, in both modes, HHO addition increases the maximum cylinder pressure and torque. With the increase of HHO flow rate, the flame development period and flame propagation period shorten, the crank angle corresponding to the maximum cylinder pressure is closer to top dead center. In addition, GDI + HHO mode has better engine performance. HHO has a significant effect on improving combustion stability. Especially at λ = 1.4, as HHO flow rate increases from 0 to 16 L/min, the coefficient of indicated mean effective pressure variation of GPI + HHO and GDI + HHO mode decreases by 69.17% and 58.29%, respectively. Moreover, HHO addition improves HC and CO emissions but increases NOx emissions. CO and HC emissions of GDI + HHO mode are the lowest under all conditions, and reaching the lowest value when HHO flow rate = 16 L/min. Besides, GDI + HHO mode not only has lower NO emissions under normal working conditions (λ = 1) but also can maintain a better combustion environment under lean-burn conditions (λ = 1.2, 1.4). In general, the application of HHO as fuel in engine can improve combustion and emission characteristics and GDI + HHO mode is the best combination of gasoline and HHO. Highlights: Two combustion systems of GDI + HHO and GPI + HHO were built in this paper. The addition of HHO optimizes the combustion of gasoline and improves torque. HHO can effectively improve combustion stability, especially under lean-burn conditions. The CO and HC emissions decrease with HHO flow rate increasing. GDI + HHO mode has better combustion and emission characteristics than GPI + HHO mode.